2008
DOI: 10.1373/clinchem.2007.094623
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pancreatic Status and Sex on Polyunsaturated Fatty Acid Profiles in Cystic Fibrosis

Abstract: Background: Some but not all studies have reported abnormal polyunsaturated fatty acid composition in cystic fibrosis (CF) patients. We investigated the influence of pancreatic status and sex on the fatty acid profile in plasma and erythrocyte membranes in patients with CF. Methods: After a 1-step transesterification with acetyl chloride on plasma and washed erythrocyte membranes, we quantified fatty acid methyl esters by use of GC-MS in 124 CF patients and 80 age-matched healthy controls. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
0
34
1
Order By: Relevance
“…In addition, Coste et al have found lower levels of this product in plasma and RBC from CF according to the pancreatic status [19]. A limitation of the study is the small number (n = 5) of patients with a FEV 1% value below 50; these patients are children or adolescents with an important respiratory deficiency that greatly affects the life expectation, and for this reason the group is poor/limited.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, Coste et al have found lower levels of this product in plasma and RBC from CF according to the pancreatic status [19]. A limitation of the study is the small number (n = 5) of patients with a FEV 1% value below 50; these patients are children or adolescents with an important respiratory deficiency that greatly affects the life expectation, and for this reason the group is poor/limited.…”
Section: Discussionmentioning
confidence: 93%
“…Strandvik et al [20] have found correlations between an altered FA profile, or levels of selected FA, and genotype, whereas Coste et al [19] found correlations between FA levels and the pancreatic status. Genotype accounts only partially for the severity of CF [25] while FEV 1 is considered the best surrogate measure for survival and therefore the best indicator of the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid composition may be influenced by genetic factors as shown in murine models (10,11) or in humans (12). The role played by pancreatic insufficiency may also be especially relevant because fat malabsorption persists in many patients despite pancreatic enzyme replacement (13).…”
mentioning
confidence: 99%
“…However, various studies show the limited impact of this routine therapy on patients' clinical conditions. In fact, a negligible improvement in anthropometric measures, an increase in saturated FAs and monounsaturated FAs, an increase in DHA/AA ratio, and onset of diabetes-type hepatic and metabolic complications have been reported (34,49,77,108). Some authors also mention significantly low levels of vitamin E associated with significantly high levels of oxysterols in patients with pancreatic insufficiency or diabetes.…”
Section: Fatty Acidsmentioning
confidence: 99%